Effect of Wetland Degradation and Conversion on Carbon Stock: The Case of Tekuma Wetland, Lake Tana Sub-Basin, Ethiopia - Yohannes Afework Kassa; Belayneh Ayele Anteneh; Temesgen Tilahun Teshome (Hasanuddin University, 2015)
Wetlands are considered as one of the major carbon sinkers that have significant positive effect on reducing the impact of climate change. However, the contribution of wetland to climate change mitigation through carbon sequestration is not well understood by the public. Many developed and developing countries signed in and supported the inclusion of agriculture and wetland projects in the Kyoto Protocol. But Ethiopian government has not yet tried to take advantage of this opportunity and start negotiations to use conservation and improvement of wetland’s carbon sequestration potential in the country to obtain carbon funds as an economic incentive for the communities involved. With this background, this research was designed to carry out an in-depth study on the impact of wetland degradation and conversion on carbon sequestration potential in Ethiopia. To meet the stated objectives stratified sampling techniques were used to select sampling sites from the wetland areas having varying wetland degradation level. For the determination of carbon levels in each area replicates of plant and soil samples were collected. The plant organic matter was determined using a loss-on-ignition method and then converted to carbon stock. Carbon stock and bulk density of the sampled soil was determined using Walkely-Black oxidation and gravimetric methods, respectively. ANOVA and mean separation were computed to indicate whether there is significant difference in carbon stock due to wetland degradation. The research findings showed significant difference (P<0.05) of carbon storage with different wetland degradation levels. Carbon stock in the soil was on average 24 times higher than carbon stock in plants in each respective wetland area having varying degradation level. The intact wetland was able to sequester579 t/ha of CO2as compared to converted farmlands and grazing lands that had only 230 and 295 t/ha of CO2, respectively. The result showed that by protecting wetlands more than double carbon could be stored as compared to grazing and farmlands. Thus, it is recommended that special attention should be given to minimize the conversion of wetlands and maximize their benefits through carbon funding.